PERANCANGAN PUSAT PENAMPUNGAN HEWAN TERLANTAR MELALUI PENERAPAN ARSITEKTUR EKOLOGIS DI JAKARTA TIMUR - Martha Ari Syahrani; Putri Suryandari; Tri Endangsih (FAKULTAS TEKNIK UNIVERSITAS BUDI LUHUR, 2021)
The abandoned animal shelter center is a place to accommodate animals that are stranded on the road, lost, or even animals that were handed over by their owners to the shelter. To then be cared for, raised until the animals get a new owner. The application of the Ecological Architecture concept to the shelter center is based on the movement for the preservation of nature and the environment for a sustainable life in the efficiency of energy and natural resources.